TEACHING READING COMPREHENSION TO THE EIGHTH GRADERS OF SMP NEGERI 53 PALEMBANG THROUGH READING, ENCODING, ANNOTATING, PONDERING (REAP) STRATEGY - Dessy Nuke Wulandari; Diemroh Ihsan; Rita Hayati (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2014)
Abstract: The study was conducted to find out whether or not there was any significant difference in reading comprehension achievement between the eighth graders of SMP Negeri 53 Palembang who were taught through REAP strategy and those who were not. The population of the study was the eighth graders of SMP Negeri 53 Palembang in the academic year 2013/2014. The total number of the students was 228 students. The sample was 76 students that were taken by using purposive sampling technique. Thirty eight students were in the experimental group and thirty eight students were in the control group. In doing this research, the writer did the experimental research by using quasi experimental design. The instrument for collecting the data was areading test that was given as a pre-test and a post-test. The result of the test that was analyzed by using the independent sample t-test analysis showed that the t-obtained value was 3.704 at the significance level p< 0.05 with df 74 and the critical value of t-table was1.993. Since the t-obtained value was higher than t-table value, that is, 3.704>1.993, the null hypothesis (Ho) was rejected and the research hypothesis (H1) was accepted. It means thatthere was a significant difference in the reading comprehension achievement between the students who were taught through REAP strategy and those who were not. Key words: REAP Strategy, Reading comprehension